Use of serum squamous cell carcinoma antigen for follow-up monitoring of cervical cancer patients who were treated by concurrent chemoradiotherapy - Yoon Sang (Radiation Oncology, 2010)
Abstract Background To investigate the significance of monitoring the levels of the serum squamous cell carcinoma antigen (SCC-Ag) for the detection of recurrent disease in patients with cervical cancer treated by concurrent chemoradiotherapy. Methods The records of 112 patients with cervical cancer were reviewed. Serum SCC-Ag levels were measured at regular follow-up visits. A SCC-Ag level of 2 ng/mL was considered the upper limit of normal. Biochemical failure was defined as two consecutively increasing SCC-Ag values above normal. Recurrent disease was confirmed by histologic and radiographic studies. Results Eighteen patients (16%) developed recurrent disease. Sixteen patients had initially elevated SCC-Ag, post-treatment normalization of SCC-Ag, and tumor recurrence. The SCC-Ag difference (ΔSCC-Ag), defined as the difference between the last value after two consecutively increases above normal and the value immediately before the elevation, had good clinical performance in predicting cancer recurrence. The cutoff value of ΔSCC-Ag was 0.95 ng/mL. Conclusions SCC-Ag is a relatively good method for the detection of disease recurrence in patients with cervical cancer who were treated by concurrent chemoradiotherapy.